2010
DOI: 10.1126/science.1179252
|View full text |Cite
|
Sign up to set email alerts
|

Anciently Asexual Bdelloid Rotifers Escape Lethal Fungal Parasites by Drying Up and Blowing Away

Abstract: Asexuality has major theoretical advantages over sexual reproduction. An important evolutionary puzzle, therefore, is why exclusively asexual metazoan lineages rarely endure. The Red Queen hypothesis posits that asexuality is rapidly extinguished by relentlessly coevolving parasites and pathogens. If so, any long-lasting asexual lineage must have unusual alternative mechanisms to deal with these biotic enemies. Bdelloid rotifers are freshwater invertebrates that abandoned sexual reproduction millions of years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 19 publications
4
54
0
Order By: Relevance
“…The most commonly recorded enemies of bdelloid rotifers are lethal fungal and oomycete parasites (ca 50 species: [37]), chiefly belonging to the genus Rotiferophthora, which preys specifically upon them. It has been demonstrated experimentally that Rotiferophthora angustispora cannot withstand desiccation or disperse by wind to the same degree as its bdelloid host, Habrotrocha elusa [26]. Desiccation for 35 days eliminated the fungus from over 90% of cultured rotifer populations, and when infected cultures were desiccated for just 7 days, but also subjected to dispersal in a wind chamber, the prevalence of parasites in newly founded populations was reduced by 60% relative to water-dispersed controls.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most commonly recorded enemies of bdelloid rotifers are lethal fungal and oomycete parasites (ca 50 species: [37]), chiefly belonging to the genus Rotiferophthora, which preys specifically upon them. It has been demonstrated experimentally that Rotiferophthora angustispora cannot withstand desiccation or disperse by wind to the same degree as its bdelloid host, Habrotrocha elusa [26]. Desiccation for 35 days eliminated the fungus from over 90% of cultured rotifer populations, and when infected cultures were desiccated for just 7 days, but also subjected to dispersal in a wind chamber, the prevalence of parasites in newly founded populations was reduced by 60% relative to water-dispersed controls.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been suggested that bdelloid rotifers may fit the requirements [22,26,27]. They are found in almost every freshwater and limno-terrestrial habitat patch worldwide, however tiny, remote or ephemeral.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it remains to be determined how often parasites elicit a coevolutionary arms race that is resolved by the host engaging in high rates of sex, or whether it is resolved by alternative mechanisms (e.g., ref. 17). Another empirical challenge is to get a better estimate of the real costs of sex across the many eukaryotic lineages.…”
Section: Discussionmentioning
confidence: 99%
“…"Ancient asexuals" are hypothesized to possess the traits to deal with such long-term challenges. Bdelloid rotifers, one of the best examples of ancient asexuality, show some characteristics that might be interpreted as alternative forms of genetic exchange (14,15), exceptional DNA repair mechanisms (16), and nongenetic means of evading fungal parasites (17).…”
Section: Asexual Invasionsmentioning
confidence: 99%